Clinical and genetic analysis of Taiwanese patients with hereditary spastic paraplegia type 5. (18th March 2014) - Lan, M.‐Y.; Yeh, T.‐H.; Chang, Y.‐Y.; Kuo, H.‐C.; Sun, H. S.; Lai, S.‐C.; Lu, C.‐S.
<x xml:space="preserve">Abstract</x> Background and purpose Spastic paraplegia type 5 (SPG5) is an autosomal recessive (AR) hereditary spastic paraplegia (HSP) associated with pure or complicated phenotypes. This study aimed to screen SPG5 in Taiwanese HSP patients. Methods Sequencing of the SPG5 gene, CYP7B1, was performed in a cohort of 25 ethnic Han Taiwanese patients with AR or sporadic HSP. Clinical information and magnetic resonance imaging (MRI) were analyzed in confirmed SPG5 patients. Results One (33%) AR kindred and four (18%) sporadic cases had CYP7B1 mutations. All of the SPG5 cases carried the mutation c.334 C>T (R112X). Haplotype analysis suggested a 'founder effect' in ethnic Hans for this mutation. The phenotype was either pure or complicated by cerebellar ataxia. For the primary HSP phenotype, there were profound dorsal column sensory deficits in all patients. Spine MRI showed thoraco‐lumbar cord atrophy in some patients. Conclusions Spastic paraplegia type 5 is a common cause of AR and sporadic HSPs that has a higher frequency in Taiwanese than in other ethnic groups. It is associated with a CYP7B1 founder mutation and its phenotype is characterized by pronounced dorsal column sensory loss, with cerebellar ataxia in some patients.